At the Frontiers of Modern Narrative: Versions of the Post-medium - Cabello Padial, Gabriel (Eikón / Imago, 2024)
This article starts from the assumption that the proposal to replace art history with a history/anthropology of images has coincided with, and has been supported by, the dissolution of the modern narrative on art and its appeal to the specific medium. We intend in this text to give an account of three approaches, those of Michael Fried, Rosalind E. Krauss and Peter Osborne. In those approaches, a dialogue is established with Clement Greenberg’s legacy, and a way out of the end of the modern narrative that differs from the one embraced by the iconic turn is proposed. Finally, we point out some of the limitations with which such Greenbergian heritage permeates these approaches, particularly the difficulty in confronting the implexité in which images and emotions are intertwined.